Energy system contribution in a maximal incremental test: correlations with pacing and overall performance in a 10-km running trial - Damasceno,M.V. (2015)
This study aimed to verify the association between the contribution of energy systems during an incremental exercise test (IET), pacing, and performance during a 10-km running time trial. Thirteen male recreational runners completed an incremental exercise test on a treadmill to determine the respiratory compensation point (RCP), maximal oxygen uptake ( V ˙ O 2 max), peak treadmill speed (PTS), and energy systems contribution; and a 10-km running time trial (T10-km) to determine endurance performance. The fractions of the aerobic (WAER) and glycolytic (WGLYCOL) contributions were calculated for each stage based on the oxygen uptake and the oxygen energy equivalents derived by blood lactate accumulation, respectively. Total metabolic demand (WTOTAL) was the sum of these two energy systems. Endurance performance during the T10-km was moderately correlated with RCP, V ˙ O 2 max and PTS (P<@0.05), and moderate-to-highly correlated with WAER, WGLYCOL, and WTOTAL (P<0.05). In addition, WAER, WGLYCOL, and WTOTAL were also significantly correlated with running speed in the middle (P<0.01) and final (P<0.01) sections of the T10-km. These findings suggest that the assessment of energy contribution during IET is potentially useful as an alternative variable in the evaluation of endurance runners, especially because of its relationship with specific parts of a long-distance race.